2022
DOI: 10.3390/md20020134
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Compounds from Alcyoniidae: An Overview of the Last 30 Years

Abstract: The octocoral family Alcyoniidae represents a rich source of bioactive substances with intriguing and unique structural features. This review aims to provide an updated overview of the compounds isolated from Alcyoniidae and displaying potential cytotoxic activity. In order to allow a better comparison among the bioactive compounds, we focused on molecules evaluated in vitro by using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay, by far the most widely used method to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 221 publications
(366 reference statements)
0
4
0
Order By: Relevance
“…Accordingly, the structure of 1 was determined as shown (Chart 1). As marine cembranoids have been proven to show a broad spectrum of biological activities, including anti-inflammatory [29], anti-oxidant [30], and cytotoxicity activities [30,31], compounds 2-19 were evaluated for their proliferation activities toward the P388, DLD-1, HuCCT-1, and CCD966SK cell lines (Table 4). Among the tested compounds, 18 exhibited the most potent activity to inhibit the proliferation of the HuCCT-1 cell with an IC 50 value of 2.0 µM, which is comparable to the positive control, doxorubicin (HuCCT-1, IC 50 = 1.9 µM), whereas compound 18 showed moderate anti-proliferation activity to P388 and DLD-1, with IC 50 s of 10.6 and 9.9 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the structure of 1 was determined as shown (Chart 1). As marine cembranoids have been proven to show a broad spectrum of biological activities, including anti-inflammatory [29], anti-oxidant [30], and cytotoxicity activities [30,31], compounds 2-19 were evaluated for their proliferation activities toward the P388, DLD-1, HuCCT-1, and CCD966SK cell lines (Table 4). Among the tested compounds, 18 exhibited the most potent activity to inhibit the proliferation of the HuCCT-1 cell with an IC 50 value of 2.0 µM, which is comparable to the positive control, doxorubicin (HuCCT-1, IC 50 = 1.9 µM), whereas compound 18 showed moderate anti-proliferation activity to P388 and DLD-1, with IC 50 s of 10.6 and 9.9 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A related analogue, isosarcophytoxide, was also reported to exhibit significant cytotoxic and moderate anti-inflammatory properties [ 30 ]. Up to date, more related derivatives have been discovered from different soft corals, and diversified biological activities of some cembranoids remain unveiled [ 3 ]. In the present study, compounds 1 – 5 were also assayed for their cytotoxicity toward human small cell lung cancer (H1688) cells, and the result showed that 3 possessed a moderate cytotoxicity (IC 50 = 27.5 ± 6.4 μM) and 4 exhibited weak activity (IC 50 = 85.8 μM) toward the H1688 cell line, while the other compounds were nontoxic with IC 50 values over 100 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Marine soft corals, in particular those of the Sarcophyton genus, have been considered to be a valuable reservoir of bioactive natural products, such as sesquiterpenoids, diterpenoids, steroids, and fatty acids [ 1 ]. Among them, the cembrane-type diterpenoids and related analogues are the most characteristic and abundant metabolites [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These structurally diversified metabolites have been reported to possess various biological activities, such as cytotoxic [ 9 , 10 , 11 ], anti-inflammatory [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], neuroprotective [ 19 ], anti-bacterial [ 19 , 20 , 21 ], and anti-viral activities [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical research of bioactive natural products has attracted a significant amount of interest. [36] Nearly 60% of the drugs approved for cancer therapy are natural products derived mainly from plants, such as vincristine (VCR), etoposide irinotecan, taxanes, and camptothecins, or from microbes, such as actinomycin D, mitomycin C, bleomycin, doxorubicin, and l-asparaginase [37].…”
Section: Terpenoidsmentioning
confidence: 99%